Organizational justice dan organizational readiness to change: Peran mediasi psychological empowerment : Organizational justice and organizational readiness to change: The mediating role of psychological empowerment - Kurniadhi, Fiergant; Ferdinandus Hindiarto (Persona:Jurnal Psikologi Indonesia, 2025)
The retail industry currently faces dynamic challenges, including market pressure, regulatory changes, and technological advancements, all of which require organizations to maintain a high level of readiness for change. This study aims to analyze the influence of organizational justice on organizational readiness to change, with psychological empowerment as a mediating variable, in a retail company in Indonesia. A quantitative approach with a cross-sectional design was employed, involving 120 respondents from lower management levels. Data were collected using the Organizational Readiness to Change scale (α = 0.890), the Psychological Empowerment scale (α = 0.915), and the Organizational Justice scale (α = 0.918) which have been validated and analyzed using the Structural Equation Modeling (SEM) method based on Partial Least Squares (PLS). The results indicate that organizational justice has a direct, positive, and significant effect on organizational readiness to change. Furthermore, psychological empowerment was found to serve as a significant mediator in the form of complementary mediation. This means that psychological empowerment complements but does not eliminate the direct effect of organizational justice. These findings highlight that the implementation of fairness principles and the strengthening of psychological empowerment are key to effectively and sustainably enhancing organizational readiness for change.